Regarding the Features of Water Flow Interaction with a Rotor Turbine - Kazbek Orazbayev; Assel Yerkongyr; Rakhimash Abitayeva; Gulmira Sakhmetova; Balnur Shashubay (Journal of Applied Engineering and Technological Science (JAETS), 2026)
The increasing demand for efficient energy production in Kazakhstan underscores the significance of optimising rotor turbines used in gravitational water vortex micro-hydroelectric power plants (MWV-MHPPs). This study addresses the challenges in rotor-flow interaction, focusing on improving turbine efficiency and mitigating performance errors. The research gap lies in the limited understanding of rotor dynamics in relation to varying water flow conditions, which directly impact turbine output. This study employs computational fluid dynamics (CFD) modelling and experimental testing to analyse the interaction between water flow and rotor turbines, focusing on key performance indicators such as torque, head loss, and flow characteristics under different operational conditions. The results indicate a 15% improvement in torque efficiency and a 10% reduction in head loss with optimised turbine blade design, compared to traditional configurations. The study also uncovers significant design flaws in existing MWV-MHPPs, contributing to energy inefficiencies in Kazakhstan’s renewable energy sector. This work proposes specific recommendations for turbine design, including enhanced blade geometry and flow regulation strategies, to mitigate these issues. The findings offer practical insights for the development of sustainable, off-grid energy solutions, contributing to the country’s energy security goals. By addressing the interaction between water flow and rotor turbines, this research advances the understanding of turbine optimisation for small-scale hydropower plants.